STUDI TENTANG BORDIR DI KOTA SUNGAI PENUH PROVINSI JAMBI - Hardianti, Witria; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research is a descriptive research with qualitative approach, which the is aims to describe the of embroidery in Sungai Penuh City, Jambi Province. The research inludes the shape of motifs, the pattern of motifs and color combinations of embroidery in Sungai Penuh City, Jambi province. Results of study revealed that: 1) Forms of embroidary motifs in the Sungai Penuh City, Jambi Province is naturalist form consists of kaluak paku, betel leaf, flower coffee, coffee leaves. 2) The decorative shape is the pattern of motifs that incung Kerinci. The patterns of motifs used in embroidery in the Sungai Penuh City, Jambi province sow ornamental paterns, decorative patterns periphery (periphery stands, periphery dependent, periphery run), free ornamental patterns and decorative patterns field. 3) The combinations of colors embroidery in the Sungai Penuh City, Jambi Province is the combinations of contrasting colors, the combinations of harmonious colors and, the combinations colors of polikromatis. Kata kunci: embroidery, Sungai Penuh City, Jambi province